Evaluating the use of Instagram images color histograms and hashtags sets for automatic image annotation - Giannoulakis, Stamatios; Tsapatsoulis, Nicolas; Djouvas, Constantinos (My University, 2023)
Color similarity has been a key feature for content-based image retrieval by contemporary search engines, such as Google. In this study, we compare the visual content information of images, obtained through color histograms, with their corresponding hashtag sets in the case of Instagram posts. In previous studies, we had concluded that less than 25% of Instagram hashtags are related to the actual visual content of the image they accompany. Thus, the use of Instagram images' corresponding hashtags for automatic image annotation is questionable. In this study, we are answering this question through the computational comparison of images' low-level characteristics with the semantic and syntactic information of their corresponding hashtags. The main conclusion of our study on 26 different subjects (concepts) is that color histograms and filtered hashtag sets, although related, should be better seen as a complementary source for image retrieval and automatic image annotation.
Keywords: Instagram hashtags; Instagram images; Histogram; Bhattacharyya distance; Word embedding; Automatic image annotation